Effects of Armed Conflict on Children Aged 12-18 Living in Post War Areas (2005-2011): A Case Study of UMYAMA Sub-County Gulu District - Nakawesa, Miriam (Mukono : Uganda Christian university, 2011)
Discriptive Cataloguing Uganda Christian University BCDCM
includes references and appendix
Keywords: Armed Conflict on Children